Integrating problem-based learning and computational thinking: cultivating creative thinking in primary education - Ji, Wancen; Wong, Gary K. W. (Frontiers in Education, 2025)
This study examines how integrating problem-based learning (PBL) with computational thinking (CT) contributes to cultivating creative thinking in senior primary school students (grades 5–6). Creativity is a critical skill for addressing complex, real-world problems, yet its development in education remains challenging. A four-week “Unmanned Supermarket” project was designed, incorporating CT skills such as problem decomposition, pattern recognition, and algorithm design. This study employed a creative thinking test tool based on Guilford’s “Structure of Intellect” model and Torrance’s “Creative Thinking Test,” contextualized for the “Unmanned Supermarket” project to ensure content relevance. Data collection involved standardized paper-based tests conducted in a classroom environment, with pre-tests and post-tests administered 1 week before and after the intervention. Data analysis included descriptive statistics, normality tests, and the Wilcoxon signed-rank test, which is appropriate for small samples with non-normal distributions. Results showed significant improvements across all five dimensions of creative thinking and the total score (p < 0.05). The most substantial gains were observed in originality and elaboration (Z = −3.547, p < 0.001; Z = −3.546, p < 0.001). Importantly, all students demonstrated higher post-test total scores compared to pre-test scores, indicating consistent overall progress. These findings demonstrate how PBL, supported by CT, can enhance specific dimensions of creativity by encouraging innovative problem-solving and iterative design. This study provides insights into designing educational interventions that promote creativity through CT and PBL integration.